Correlation between severe coronary stenosis and recurrence after atrial fibrillation cryoablation - LUO Xiaoying, DONG Fengwei, XU Yan, WU Liqun, QI Wenhang (Zhenduanxue lilun yu shijian)
Objective To investigate the correlation between severe coronary stenosis detected by coronary CT angio-graphy (CCTA) before cryoablation and atrial fibrillation (AF) recurrence. Methods From January 2021 to November 2022, 613 consecutive patients with symptomatic paroxysmal or persistent AF undergoing first-time cryoablation and successful preprocedural CCTA screening were enrolled. Severe coronary stenosis on CCTA was defined as >70% stenosis in at least one major coronary vessel. Patients were divided into two groups: severe stenosis group (n=53) and non-severe stenosis group (n=560). All patients were regularly followed up after ablation to observe safety endpoints such as AF recurrence and surgical complications. Kaplan-Meier analysis was used to assess AF-free survival rate, and multivariate Cox regression was performed to identify predictors of AF recurrence. Results 22.5% of patients were diagnosed with coronary heart disea-se (CHD), of whom 8.6% (53/560) had severe stenosis on pre-ablation CCTA. Compared to the non-severe stenosis group, the severe coronary stenosis group had higher age [(69.6±10.3) years vs. (62.3±11.9) years], higher prevalence of persistent AF (59.3% vs. 31.6%), higher CHA2DS2 -VASc score (2.3±1.6 vs. 1.5±1.4), lower left ventricular ejection fraction (LVEF) [(48.8%±10.3%) vs. (57.2%±8.9%)], higher left atrial volume index (LAVI) [(50.3±11.7) mL/m² vs. (37.0±12.3) mL/m²], and higher E/A ratio (1.6±0.4 vs. 1.1±0.5) (all P<0.05). Among the 53 patients with severe stenosis detected by CCTA, 50 (94.3%) were newly diagnosed with CHD. After a median follow-up of 28 months, the AF recurrence rate was 20.1% (123/613). The severe stenosis group showed an AF recurrence rate of 35.8% (19/53), significantly higher than the 18.6% (104/560) in the non-severe stenosis group (P<0.05). There was no statistically significant difference in the safety endpoint between the two groups (P>0.05). Kaplan-Meier analysis showed lower AF-free survival rate in the severe stenosis group (71.6% vs. 84.8%, P=0.039). Multivariate Cox regression identified age (OR=1.20, 95%CI: 1.09-1.39, P=0.033), persistent AF (OR=2.750, 95%CI: 1.64-5.37, P=0.001), and LAVI (OR=1.14, 95%CI: 1.10-1.38, P=0.008) as independent predictors of AF recurrence. Conclusions Patients with severe coronary stenosis before ablation screening have lower AF-free survival rate, but severe coronary stenosis itself is not an independent predictor of AF recurrence after cryoablation.